(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A long fiber that is often constructed of glass or plastic is used in optical fiber technology to transmit data utilizing short light pulses. Signal loss is reduced by metal wires; hence they are preferable for transmission in optical fiber communications. The problem arises to other cable such as inadequate transmission power excessive signal loss brought on by an excessively lengthy wire span. Signal loss that is too great because to damaged connections. Excessive signal loss as a result of a bad connection or splice. Hence all these this problem overcomes with help of optical fiber such as to transport data, fiber optic cables include a core that conveys light. In comparison to copper connections, fiber optic cables can now transmit messages at rates that are just 31% slower than the speed of light. In this paper author discussed the working principle of optical fiber, types of optical fiber, and its application in different sectors. It concluded that the use of optical fiber cable in communication networks has become increasingly popular, and a dizzying number of suppliers are now vying to produce and provide fiber optic cables. In the future, more and more automobiles are using fiber optics due to its ability to save space and provide greater illumination, and fiber optic technology is anticipated to play a significant role in this expansion.